THE ROLE OF THE SERVICE SECTOR IN POVERTY REDUCTION AND EMPLOYMENT GROWTH - Fozilov Vahobjon Akrom o’g’li (TADQIQOTLAR, 2026)
Annotation. This article examines the role of the service sector in poverty reduction and employment growth within the modern economy. The study analyzes the contribution of service industries to economic development, income generation, labor market expansion, and improvement of living standards. Particular attention is given to the importance of tourism, finance, trade, education, healthcare, and digital services in creating new jobs and increasing household incomes. The article also explores government policies and institutional mechanisms aimed at supporting the service sector as an important tool for sustainable economic growth and poverty alleviation.